STORY-BASED READING: AN EXPLORATIVE CASE STUDY OF STUDENTS’ ORAL RESPONDING IN THE EFL CLASSROOM - Junjun Muhamad Ramdani; Melisa Sri; Tiffany Dewi; Resna Suci Faradilah (TLEMC (Teaching and Learning English in Multicultural Contexts), 2017)
This study discusses how students’ story and story-based reading can stimulate their oral responding to students of non-English Department. Exchanging life experience was used as a task that stimulated the students to share ideas based on the story they read. This activity was intended to encourage them to speak and explore their management skill. The action done would affect their oral responding, specifically fluency. Employing qualitative method, this study involves eleven out of forty first-year students of non-English Department at Siliwangi University. The authors illustrate how the activities were employed in the class and the students’ impressions taken from written responses. This study is a reflection developing teachers’ innovation and creativity in the EFL Context